The Effect of Workload and Social Support on Burnout in Employees of the Bandung Regency Regional Revenue Agency - Ega Rulli Raharja; Pras Rendy (Psikologi Prima, 2026)
Burnout is a chronic condition in the form of emotional, mental, and physical fatigue caused by long-term work pressure. This study aims to examine the influence of workload and social support on burnout in employees of the Regional Revenue Agency (BAPENDA) of Bandung Regency. The quantitative research design was used with multiple linear regression analysis. Data was collected from 80 employees who were selected through purposive sampling techniques. The results showed that workload had a significant effect on burnout (β = −0.868; t = −68.479; p < 0.001), while social support also significantly affected burnout (β = 0.493; t = 38.865; p < 0.001). The negative coefficient for workload indicates an inverse relationship in the coding direction of the measurement scale used in this study. In other words, lower scores on the workload scale represented higher perceived workload, which statistically produced a negative coefficient. Therefore, substantively, the findings still indicate that higher workload is associated with increased burnout among employees. Simultaneously, workload and social support accounted for 98.7% of the burnout variance (F = 3,075,171; p < 0.001; Adjusted R² = 0.987). These findings confirm the Job Demands-Resources (JD-R) model and affirm the importance of balanced workload management and strengthening social support systems in preventing employee burnout in public sector organizations.